Transforming FDI Narratives in SAARC: COVID-19’s Impact and India’s Rising Advantage - Firdos, Rizwan; Mansuri, Babu Bakhsh (South Asian Journal of Social Sciences and Humanities, 2025)
Foreign direct investment (FDI) is the most important source of funding for South Asian Association for Regional Cooperation (SAARC) countries as it allows them to seize numerous development opportunities. Because of the uncertainty brought by COVID-19, the global economy, including developed and developing countries, has been experiencing some changing trends in FDI in recent years. This investigation aims to find the effects of the COVID-19 pandemic on FDI inflows in SAARC countries. The study further analysed the business environments of SAARC countries. The study is descriptive and analytical in nature. Secondary data like World Bank reports and UNCTAD reports are used in the study. The study concludes that pandemic COVID-19 has a negative impact on FDI in SAARC countries except India. However, most of the SAARC countries have shown upward trends in FDI inflows in the post-COVID-19 period. In terms of the business environment, India is regarded as the most advantageous location and favourable destination for foreign investors. While Bangladesh, Nepal, and Pakistan are more attractive countries for FDI inflow.